ANALISIS KELEMBAGAAN PENGENDALIAN HAMA TERPADU MENDUKUNG AGRIBISNIS KOPI RAKYAT DALAM RANGKA OTONOMI DAERAH - SAPTANA -; HERLINA TARIGAN; ADI SETIANTO (SOCA: Jurnal Sosial Ekonomi Pertanian, 2005)
Integrated Pest Management Program (IPM) that is strategic operational measure. Inthe micro farm level, IPM operational measure can be answered both capital problem in thefarm level and international commodity coercion on environmental and food safetyconsumption simultaneously. That paper objective to analysis : (1) historical governmentpolicy on IPM related the decentralization of development; (2) performance, constrain, andprospective IPM program in the decentralization era; (3) comparative farming performanceIPM cooperator, inter success farms group and least success farms group; (4) factors thataffected dissemination and adoption IPM technology; (5) synopsis on IPM sustainableinstitution in the decentralization era; and (6) to formulate police IPM sustainabledevelopment alternative supporting small coffee agribusiness in the decentralization era.Rates of participation of the IPM program participants varied among activities, i.e., planning,implementation, monitoring and evaluation. Low participation rate was found in planning,that of implementation was high, while that of monitoring and evaluation was low tomoderate. Program explanation during the planning stage was not properly carried out. Theother weaknesses were management of post harvest, processing, and marketing. After theIPM program average net benefits from coffee bean and additional in-rows plants were toincrease, respectively. Economic factors positively affecting IPM technology adoption were:(1) decreasing costs of inputs (fertilizers and pesticides); (2) improving farmers’ incomethrough higher yield and better quality; (3) improving stability and continuity of farmers’income due longer harvest and productive periods, and the products were sold periodically.In the future, development of IPM program for smallholding coffee plantation is based on theclear vision, namely IPM technology for improving rural people welfare. This vision has toreplace the old vision, namely IPM technology is created just to show that the researchers areable to show their ability in developing technology. Therefore, in the future IPM developmenthas to implicate directly to improved competitive economy and rural people welfare.